Carbapenem Resistance in Acinetobacter baumannii and Other Acinetobacter spp. Causing Neonatal Sepsis: Focus on NDM-1 and Its Linkage to ISAba125 - Chatterjee, Somdatta; Datta, Saswati; Roy, Subhasree; Ramanan, Lavanya; Saha, Anindya; Viswanathan, Rajlakshmi; Som, Tapas; Basu, Sulagna (Frontiers in Microbiology, 2016)
Carbapenem-resistant determinants and their surrounding genetic structure were studied in Acinetobacter spp. from neonatal sepsis cases collected over 7 years at a tertiary care hospital. Acinetobacter spp. (n=68) were identified by ARDRA followed by susceptibility tests. Oxacillinases, metallo-β-lactamases (MBLs), extended-spectrum β-lactamases and AmpCs, were detected phenotypically and/or by PCR followed by sequencing. Transconjugants possessing the blaNDM-1 (New Delhi metallo-β-lactamases) underwent further analysis for plasmids, integrons and associated genes. Genetic environment of the carbapenemases were studied by PCR mapping and sequencing. Multivariate logistic regression was used to identify risk factors for sepsis caused by NDM-1-harbouring organisms. A. baumannii (72%) was the predominant species followed by A. calcoaceticus (10%), A. lwoffii (6%), 13TU (3%), A. junni (3%), 15TU (3%), A. haemolyticus (2%) and 14TU (2%). Fifty six percent of the isolates were meropenem-resistant. Oxacillinases present were OXA-23-like, OXA-58-like and OXA-51-like, predominately in A. baumannii. NDM-1 was the dominant MBL (22%) across different Acinetobacter spp. Isolates harbouring NDM-1 also possessed bla(VIM-2, PER-1, VEB-2, CTX-M-15), armA, aac(6’)Ib, aac(6’)Ib-cr genes. blaNDM-1 was organised in a composite transposon between two copies of ISAba125 in the isolates irrespective of the species. Further, OXA-23-like gene and OXA-58-like genes were linked with ISAba1 and ISAba3 respectively. Isolates were clonally diverse. Integrons were variable in sequence but not associated with carbapenem resistance. Most commonly found genes in the 5’ and 3’conserved segment were aminoglycoside resistance genes (aadB, aadA2, aac4’), non-enzymatic chloramphenicol resistance gene (cmlA1g) and ADP-ribosylation genes (arr2, arr3). Outborn neonates had a significantly higher incidence of sepsis due to NDM-1 harbouring isolates than their inborn counterparts. This study demonstrates the significance of both A. baumannii and other species of Acinetobacter in cases of neonatal sepsis over an extended period. Oxacillinases and NDM-1 are the major contributors to carbapenem resistant. The dissemination of the blaNDM-1 is likely linked to Tn125 in diverse clones of the isolates.